Performance of hybrid maize (Zea mays L.) under varying phosphorus and potassium levels - Choudhary, K.M.; Chouhan, D.; Singh, D.; Nepalia, V. (Annals of Agricultural Research, 2018)
A field experiment was conducted at Udaipur during kharif 2015, with objective to work out optimum phosphorus and potassium levels for hybrid maize. The treatment consisted combinations of four phosphorus levels (30, 45, 60 and 75 kg K2O5 ha–1) and four potassium levels (30, 40, 50 and 60 kg K2O ha–1). The results revealed that application of 60 kg P2O5 ha–1 significantly enhanced growth and yield attributing parameters. Consequently grain, stover, biological yields, nutrient uptake, protein content of grain and stover and available P status of soil were significantly higher under 60 kg P2O5 ha–1 over 45 and 30 kg P2O5 ha–1. With highest net returns (` 38593 ha–1) and B C ratio (1.75), 60 kg P2O5 ha–1 proved economically profitable compared to rest of the levels. Application of increasing levels of P2O5 significantly decreased soil N status. Likewise application of 40 kg K2O ha–1 significantly improved growth, yield attributes, yield, protein content of grain and stover, profitability and soil K status over 30 kg K2O ha–1. Further increase in K2O levels failed to record statistical significance.